Potential Role of CREM in Diabetes‐Associated Testicular Dysfunction: Current Evidence and Future Perspectives - Olabimpe Caroline Badejogbin; Oyedayo Phillips Akano; Oluwafisayo Elizabeth Boluwatife Julius; Mary Olaoluwa Agunloye; Makinde Vincent Olubiyi; Ojichukwuka Ebere Chijioke‐Agu; Matthew Agene Obekpa; Adesina Paul Arikawe; Kehinde Samuel Olaniyi (Reproductive Medicine and Biology)
ABSTRACT Background Type 2 diabetes mellitus (T2D) is a growing metabolic disorder affecting all age groups and is linked to testiculopathy, a key contributor to male infertility. Testiculopathy disrupts spermatogenesis and the sperm microenvironment, with the cyclic adenosine monophosphate (cAMP) response element modulator (CREM) playing a pivotal role in testicular function. Understanding the interplay between T2D and CREM dysregulation is essential for developing targeted therapies for diabetic testicular dysfunction. Methods A systematic review of PubMed, Web of Science, Scopus, and Google Scholar was conducted to identify peer‐reviewed studies, both preclinical and clinical, that explored CREM's role in diabetes‐induced testicular dysfunction. Extracted data focused on CREM expression, oxidative stress, apoptosis, and spermatogenic impairment in diabetic models. Main Findings Research from studies on diabetic patients and animal models highlights the detrimental effects of diabetes on the reproductive system, including hypothalamic–pituitary–testicular (HPT) axis dysregulation. CREM regulates spermatogenic gene expression, influenced by luteinizing hormone (LH), follicle‐stimulating hormone (FSH), and cAMP signaling. Conclusion CREM has a therapeutic role in maintaining testicular function, and its disruption may contribute to testiculopathy in T2D, highlighting its potential therapeutic target for preserving male fertility in diabetic patients. Further research is needed to explore its molecular mechanisms and therapeutic implications.